Obstetric forceps dimensions and the newborn head biometry: Time for an update - Ismail, Abdul-Qader T; Fritze, Anne; Rüdiger, Mario; Ismail, Khaled M (European journal of obstetrics, gynecology and reproductive biology, 2021)
Obstetric forceps were invented in the 1600s to assist vaginal delivery of term babies following prolonged labour. This probably explains their design, with a narrow interblade distance and long blade length, to fit a severely moulded fetal head. However, in modern obstetric practice protracted labour is avoided, yet our research has shown that over 400 years forceps dimensions have remained largely unchanged. We believe it is time to optimise these dimensions based on biometry of the term, newborn baby's head, with the head width (biparietal diameter) and head length (mentovertical diameter) correlating with interblade distance and blade length respectively. We hypothesise that doing so should reduce the incidence of neonatal complications associated with forceps assisted delivery and it is also possible that the amended shape might be associated with better outcomes for women. In this article we present our rationale for the optimisation of the forceps dimensions based on the findings of our previous systematic review and an original series of mentovertical and biparietal diameter measurements using laser scanning technology.
Keywords: biometrie; lidé; hlava; Female; Infant, Newborn; Labor, Obstetric; Pregnancy; Head; porodní děj; těhotenství; novorozenec; porodnické kleště; Delivery, Obstetric; vedení porodu; Obstetrical Forceps; ženské pohlaví; Biometry; Humans